Seeing the Success Through the Failure: A Lesson in Social Justice - Savelli, Melanie (Carolinas Communication Annual, 2021)
Keywords: dept.com; ⛔ No DOI found

Improve Message Design Using Catch Phrase - Savelli, Melanie (Journal of the Communication, Speech & Theatre Association of North Dakota, 2021)
Keywords: dept.com; ⛔ No DOI found

Improving Psychological and Emotional Well-Being of the First-Year College Students - Robinson, Dyan; Yavuz, Olcay (FIRE: Futuristic Implementations of Research in Education, 2021)
Almost half of the students who begin college are not retained at the institution in which they began. The purpose of this research was to explore the perceptions of first-year college students to improve their psychological and emotional well-being.  This quantitative study utilized the College Student Mentoring Scale that includes two interrelated constructs which are, Psychological and Emotional Support and The Existence of a Role Model. The research found that multiple factors impact first-year students' perceptions of their psychological and emotional well-being. Additional findings indicated that response levels were highest for The Existence of a Role Model.  It is the intention that this study will add to the somewhat limited research on improving the psychological and emotional well-being of first-year college students in higher education. Also, it will assist in future policies and practices by providing a foundation of the components that influence first-year student success through improving the effectiveness of peer mentoring programs.
Keywords: dept.com; dept.edl; dept.fye; first-year college students; peer-reviewed; ⛔ No DOI found

The impact of mass media-delivered family planning campaigns in low- and middle-income countries: A meta-analysis of advertising and entertainment-education format effects - Rogers, Dana; Snyder, Leslie B.; Rego, Michelle M. (Studies in family planning, 2021)
Effective family planning methods are shown to save lives, contribute to gender equality, and boost economic development. Mass media communication campaigns in low- and middle-income countries have been effective in increasing contraceptive use, although the strategies that increase the likelihood of success are unclear. The present study uses meta-analyses to uncover the average effect of media campaigns on family planning behaviors in low- and middle-income countries and to examine the effectiveness of two communication strategies: entertainment-education and advertising/public service announcements. Results indicated that mass media-delivered family planning campaigns have a positive impact on family planning behaviors: d = 0.19, 95% CI [0.15, 0.24] for women (k = 64), d = 0.16, 95% CI [0.11, 0.21] for men (k = 27), and d = 0.20, 95% CI [0.17, 0.23] for an undifferentiated target group of men and women (k = 37). The use of an entertainment-education format, often in addition to campaign advertising messages, was associated with greater campaign success rates for women. Men, however, responded negatively to education-entertainment and positively to campaigns using only advertising and public service announcement formats. Recommendations for future family planning mass media campaigns and academic research opportunities are discussed. © 2021 The Population Council, Inc.
Keywords: adult; advertising; article; contraceptive use; dept.com; developing world; education; family planning; female; human; human experiment; male; mass media; mass medium; meta analysis; meta-analysis; middle income country; peer-reviewed; public service announcement; type D behavior